Endocrine system at a glance - Ben Greenstein (Blackwell Science, 1994)
Endocrinology at a Glance is designed to be a concise, readily accessible introduction and revision aid for undergraduate medical and science students. The book follows the popular, easy-to-use at a Glance format, presenting each topic as a double-page-spread. Clear, informative diagrams are accompanied by key facts to explain the mechanisms and principles of endocrinology. For ease of understanding, the book is divided into sections based on the main endocrine organs. Each section explains organ anatomy, hormone production, storage and control of release, receptors, antagonists, mechanism of action, effects and inactivation. The clinical application of scientific concepts is emphasized throughout the book